Singapore fling with the millionaire - Douglas, Michelle (Harlequin Romance, 2020)
Designer Christy Minslow's put everything into her fashion brand. Now she wants to focus on her designs, not balancing the books. When billionaire James Cooper-Ford invites her to discuss buying her out, she's intrigued! After a past bitter betrayal, she's cautious of James's reputation. But in reality, there's more to him than meets the eye. He's funny, charming, attractive- and quite possibly just the holiday fling she needs!